Determinants Factors of Pre-Eclampsia Incidence - Sri Rahayu; Endah Kamila Mas'udah; Lisa Purbawaning Wulandari (Journal of Ners and Midwifery, 2022)
Maternal Mortality Rate (MMR) is one indicator in describing the welfare of society in a country. MMR in Indonesia in 2020 has increased compared to 2019. In 2019, MMR in East Java Province reached 89.81 per 100,000 live births. This figure will increase in 2020 to 98.39 per 100,000 live births. An important issue in Malang Regency related to maternal and child health is the high MMR. Preeclampsia is the 3rd largest case along with cases of infection and postpartum bleeding. The purpose of this research was to see a description of the determinants associated with the incidence of preeclampsia and to find the most dominant determinants causing preeclampsia in Kanjuruhan Hospital, Malang Regency. The type of the research was descriptive with a documentation study approach from the medical records of RSUD Kanjuruhan Malang. The analysis technique used descriptive analysis. The results of the research showed that the age data of most of the pregnant women were in high risk age (more than 35 years) as many as 28 mothers (56%), the distance between pregnancies in pregnant women with preeclampsia was mostly more than 2 years (64%), the highest parity of women with preeclampsia was multipara (68%), most of the women had never had an abortion (72%) and the gestational age of most women with preeclampsia was term (76%). Factors that determine the incidence of preeclampsia are age, gestation interval, parity and gestational age. Further research is needed to determine other factors that cause preeclampsia.